Feeding Your Mind, Improving Your Writing - Nancy Rocío Pinzón Ramírez; Aura Victoria Ramos (Universidad de La Sabana, 2009)
The central concern of the present investigation is to guide high school students to learn and write paragraphs using the traffic signal colours mnemonic technique while studying biotechnology topics. These students participated actively in laboratory experiments, practical workshops and computer classroom sections. They expanded their knowledge and written practice using the resources compiled in a web page and sending some of their compositions via e-mail. From the paragraphs created and corrected by students themselves, it is possible to assert that the "Step Up to Writing" program and content-based instruction provided them with a very useful path to improve both their writing skills and their knowledge about food.